2012
DOI: 10.1007/s11999-011-2060-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators in Pediatric Orthopaedic Surgery: A Systematic Review

Abstract: Background The ability to measure health system quality has become a priority for governments, the private sector, and the public. Quality indicators (QIs) refer to clear, measurable items related to outcomes. The use of QIs can initiate local quality improvement and track changes in quality over time as interventions are implemented. Questions/purposes We identified existing evidencebased indicators of quality pediatric orthopaedic care and evaluated published QIs that may be applicable to pediatric orthopaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, there is an increasing demand to define measures of outcomes to improve surgical quality. Most used quality indicators in pediatric surgery are mortality, morbidity, unplanned readmissions, and the incidence of postoperative complications [ 3 , 4 ]. Many of those, such as mortality and morbidity, are often not applicable to the pediatric population because the incidence of those events is too low in children [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an increasing demand to define measures of outcomes to improve surgical quality. Most used quality indicators in pediatric surgery are mortality, morbidity, unplanned readmissions, and the incidence of postoperative complications [ 3 , 4 ]. Many of those, such as mortality and morbidity, are often not applicable to the pediatric population because the incidence of those events is too low in children [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excluded as the study design was not in the inclusion criteria: systematic review article Kennedy et al (53) Quality indicators in paediatric surgery: a systematic review…”
Section: Discussionmentioning
confidence: 99%
“…36 In a systematic review, Kennedy et al found that mortality and postoperative complications were the most commonly reported quality indicators after pediatric orthopedic surgery. 37 While process measures may be employed in CEAs, there is no feasible way to convert them to QALY or utility, precluding their use in CUAs.…”
Section: Outcome Measures and Process Measuresmentioning
confidence: 99%